Automatic power factor and speed control of three phase induction motor using programmable logic control - B. Venkatramanan, C; Padma, S (International Journal of Engineering and Technology, 2018)
This paper proposes an efficient speed control and power factor improvement of three phase induction motor using PLC. Hardware and software are implemented in this work. The hardware consists of power-circuit and control-circuit of the working system and software PLC programs were developed. Power factor correction is applied to enhance the efficiency of transmission network. Three phase induction motor is used which acts as inductive load which produce variation in power factor. The power factor of the supply line is directly monitored by the Multi-Function Meter which is connected in parallel to the supply line. The value of the capacitance (capacitor bank) for correcting the power factor variation due to induction motor is found out separately. Capacitor bank for the respective load is triggered by using PLC, which connects the capacitor bank parallel to the load and thereby bringing the power factor nearly to unity. The speed of the motor can also be varied from minimum value to the rated value by VF method. The results obtained prove that the power factor can be improved automatically and also accurate speed control can be obtained.